Use of growth regulator in reducing the size of Sesbania punicea (Cav.) Benth. - Grzeça, Gislaine Tais; Winhelmann, Mara Cintia; Emer, Aquélis Armiliato; Tedesco, Marília; Lazarotto, Marília; Schafer, Gilmar (Acta Iguazu, 2021)
Sesbania punicea (Cav.) Benth. is a species with ornamental potential, highlighted by the orange color of the flowers and the formation of inflorescences in racemes. Because it is a native species and few plant breeding information, studies are needed to be used commercially, one of the aspects to be investigated is the reduction of its size for potting. The objective was to evaluate the influence of daminozide in reducing the size of Sesbania punicea. The seedlings were grown in 2.8 L pots containing substrate based on pine bark. A completely randomized design was used, with 3 treatments, 1 control, with 4 replications, 5 plants per plot. The treatments consisted of daminozide in doses of 2, 4 and 6 g L⁻¹ and control (water + 1 mL L⁻¹ adhesive spreader) that were sprayed using a 2 L accumulated pressure sprayer on the plants on the 22nd and 44th days after transplant. At the end of the experiment, height, stem diameter, dry matter of shoot and roots, chlorophyll a, b and total, number of leaves and internodes were evaluated. There were significant differences for plant height, stem diameter, number of leaves per plant and shoot dry matter. It is concluded that the dose of 5.8 g L⁻¹ of daminozide showed superior results for the reduction the size of this species.